2009
DOI: 10.1002/gps.2347
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics and risk of cerebrovascular events in treatment of behavioural and psychological symptoms of dementia in Hong Kong: a hospital‐based, retrospective, cohort study

Abstract: This study showed that there was no statistical difference in risk of cerebrovascular events in treatment of BPSD with typical and atypical antipsychotics compared with non-user group. Nonetheless, given the side effects of antipsychotics, prescription of antipsychotics should be reserved for severe and distressing symptoms with careful consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Gill et al followed patients with dementia for an average of eight months and found no difference in risk [11] (HR = 0.99; 95%CI 0.79 to 1.23) even among high-risk subgroups defined by history of stroke or long-term care residence. A study based in Hong Kong followed dementia patients for an average of 2.4 years and also found no difference in risk [16] (HR = 0.93; 95%CI 0.52 to 1.67). These results may be explained by these studies' longer periods of follow-up, particularly if high-risk FGA patients experience stroke only during the first few months after antipsychotic initiation or if such patients were more likely to discontinue or switch their antipsychotic medication, which were both treated as censoring events in these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Gill et al followed patients with dementia for an average of eight months and found no difference in risk [11] (HR = 0.99; 95%CI 0.79 to 1.23) even among high-risk subgroups defined by history of stroke or long-term care residence. A study based in Hong Kong followed dementia patients for an average of 2.4 years and also found no difference in risk [16] (HR = 0.93; 95%CI 0.52 to 1.67). These results may be explained by these studies' longer periods of follow-up, particularly if high-risk FGA patients experience stroke only during the first few months after antipsychotic initiation or if such patients were more likely to discontinue or switch their antipsychotic medication, which were both treated as censoring events in these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The few studies that avoided these potential biases reported higher first-generation antipsychotic risk for ventricular arrhythmia 33 , myocardial infarction 33,34 and hip-fracture, 34,35 but lower risk for venous thromboembolism. But the evidence for stroke was mixed 33,34,36-39 and none reported a difference in risk for pneumonia or other bacterial infections. 33-35 The divergent evidence for hip fracture and pneumonia may be partly explained by our focus on community-dwelling older adults to improve internal validity for comparisons across events, whereas many other studies focused on or included nursing home residents.…”
Section: Discussionmentioning
confidence: 99%
“…25 All studies included adult participants, 8 of which focused on elderly patients, 16,19,36e39,41,42 and 5 of which included patients with dementia. 16,19,38,41,42 Characteristics of individual studies are summarized in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Only 1 study performed CVA diagnosis validation from reviewed medical records. 42 The studies also varied in the adjusted covariates. All studies comprehensively adjusted for potential confounders in their analysis.…”
Section: Study Qualitymentioning
confidence: 99%